2022
DOI: 10.3389/fbioe.2022.1046476
|View full text |Cite
|
Sign up to set email alerts
|

Global trends and current status of distraction osteogenesis: Bibliometric analysis of publications from 1980 to 2021

Abstract: Introduction: Distraction osteogenesis (DO) has become an important technology for the correction of various congenital and acquired skeletal ridge deformities. It is widely used in oral and maxillofacial surgery, orthopedics, and other disciplines. From 1980 to 2021, the cutting-edge research of DO has been continuously promoted, and the interaction between disciplines has also been deepening. However, the analysis on the global trend and status of DO is relatively rare. Therefore, the aim of our study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…There are three possible explanations for this discrepancy: [ 1 ] Like the majority of studies that reported an average union time within one year using the Masquelet technique, the length of the bone defect was generally approximately 5 cm [ 16 ] [ 2 ]. This may be attributed to case-specific variations given the small sample size in this study [ 3 ]. The extensive duration of the study may also contribute to a potential bias in the surgical protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three possible explanations for this discrepancy: [ 1 ] Like the majority of studies that reported an average union time within one year using the Masquelet technique, the length of the bone defect was generally approximately 5 cm [ 16 ] [ 2 ]. This may be attributed to case-specific variations given the small sample size in this study [ 3 ]. The extensive duration of the study may also contribute to a potential bias in the surgical protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Such fractures are accompanied by blood vessel rupture, skin and soft tissue defects, and bone exposure, which increase the complexity of the situation and the difficulty of surgical treatment [ 1 ]. The ilizarov bone transport technique, a method of distraction osteogenesis, has been widely adopted for two decades to treat bone losses larger than 40 mm [ 2 , 3 ]. The alternate technique is to place a vascularized bone graft with blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“… 4 In recent years, thanks to the availability of computer analysis software and the increase in the number of publications, the research efficiency and accuracy of bibliometrics have been improved, and the results can be presented more intuitively through software visualization, making bibliometrics a widely used research method. and these tools have been widely used in medical fields, such as oncology, 5 Orthopedics, 6 Hypertension, 7 and Dermatology. 8 Although a few of bibliometric studies on psoriasis have been conducted in recent years, they are either regional studies 9 or only focused on nail psoriasis, 10 A comprehensive bibliometric study of global psoriasis research has not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Given that a full recovery can take up to two years [8], the biomechanical complexities introduced by these changes are challenging to evaluate during the initial surgery, resulting in a lack of comprehensive study and documentation. In fact, there is a gap in the existing literature regarding the exploration of how various types of defects can impact mandibular function [9].…”
Section: Introductionmentioning
confidence: 99%